(untitled) (Mustansiria Dental Journal, 2005)
The introduction of adhesives has created a new opportunity to bond composite resin to existing amalgam restoration on aesthetically disturbing surfaces. Further more , the composite laminate would probably improve the restoration . This in vitro study was conducted to evaluate the shear bond strength of composite resin to fresh and set amalgam by the use of two adhesive systems and to study the effect of water storage time on the shear bond strength of composite resin to fresh and set amalgam One hundred and eighty cylindrical specimens, 5mm high x 5 mm in diameter , composed of 3 mm of amalgam and 2 mm of composite with a layer of bonding material in between were prepared. Syntac Sc, Excite, control (non bonding) used to bond composite resin (Tetric) to the amalgam bases in three groups I, Il and lll (each one composed of 60 amalgam bases). Each group divided into two minor groups each of 30 amalgam bases one for fresh amalgam bases referred (F) and the other one for set amalgam bases referred (S), each minor group, F and S subdivided into 3 subgroups according to water immersion period into 48hrs, lmonth, 3months,stored at 37 C for scheduled period of time .